VD_FINDINFO Décision / 2012 / 804 vom 19. September 2012 - VD Tribunal cantonal (2012)
AVANCE DE FRAIS, DÉCISION D'IRRECEVABILITÉ, RADIATION DU RÔLE | 69 al. 1bis LAI, 61 let. a LPGA, 47 al. 2 LPA-VD, 47 al. 3 LPA-VD